Research Directions in the Clinical Implementation of Pharmacogenomics: An Overview of US Programs and Projects. Issue 5 (30th March 2018) - Volpi, Simona; Bult, Carol J.; Chisholm, Rex L.; Deverka, Patricia A.; Ginsburg, Geoffrey S.; Jacob, Howard J.; Kasapi, Melpomeni; McLeod, Howard L.; Roden, Dan M.; Williams, Marc S.; Green, Eric D.; Rodriguez, Laura Lyman; et al.
Abstract : Response to a drug often differs widely among individual patients. This variability is frequently observed not only with respect to effective responses but also with adverse drug reactions. Matching patients to the drugs that are most likely to be effective and least likely to cause harm is the goal of effective therapeutics. Pharmacogenomics (PGx) holds the promise of precision medicine through elucidating the genetic determinants responsible for pharmacological outcomes and using them to guide drug selection and dosing. Here we survey the US landscape of research programs in PGx implementation, review current advances and clinical applications of PGx, summarize the obstacles that have hindered PGx implementation, and identify the critical knowledge gaps and possible studies needed to help to address them.